2016
DOI: 10.18632/oncotarget.13895
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 and its ligands are important immune checkpoints in cancer

Abstract: Checkpoint programmed death-1 (PD-1)/programmed cell death ligands (PD-Ls) have been identified as negative immunoregulatory molecules that promote immune evasion of tumor cells. The interaction of PD-1 and PD-Ls inhibits the function of T cells and tumor-infiltrating lymphocytes (TIL) while increasing the function of immunosuppressive regulatory T cells (Tregs). This condition causes the tumor cells to evade immune response. Thus, the blockade of PD-1/PD-L1 enhances anti-tumor immunity by reducing the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
222
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(233 citation statements)
references
References 140 publications
(192 reference statements)
2
222
1
8
Order By: Relevance
“…Among them, PDCD8 and PDCD9 are officially known as AIFM1 and MRPS30, respectively. PDCD1, often known as PD-1, is the member that has been most extensively studied and shown to negatively regulate T cell responses, in collaboration with its two ligands, PD-L1 and PD-L2 (51)(52)(53). In addition to PDCD5, other programmed cell death proteins are also known to play important roles in apoptosis and/or cell cycle progression (54)(55)(56)(57), and are also dysregulated in many types of human cancers (13,16,(58)(59)(60)(61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, PDCD8 and PDCD9 are officially known as AIFM1 and MRPS30, respectively. PDCD1, often known as PD-1, is the member that has been most extensively studied and shown to negatively regulate T cell responses, in collaboration with its two ligands, PD-L1 and PD-L2 (51)(52)(53). In addition to PDCD5, other programmed cell death proteins are also known to play important roles in apoptosis and/or cell cycle progression (54)(55)(56)(57), and are also dysregulated in many types of human cancers (13,16,(58)(59)(60)(61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…Programmed death 1 (PD-1), also known as cluster of differentiation (CD)279, is an immune receptor belonging to the immunoglobulin superfamily (5,6). PD-1 is expressed on several immune cells, particularly activated T cells, B cells and myeloid cells, to modulate their activation or inhibition (6).…”
Section: Introductionmentioning
confidence: 99%
“…PD-1 has two ligands, programmed death ligand 1 (PD-L1), also known as B7 homolog 1 or CD274, and PD-L2 (B7-DC or CD273). PD-L2 is expressed predominantly on macrophages and dendritic cells, whereas PD-L1 is expressed on tumor cells and other immune cells (5,6). It was demonstrated that the inhibitory effect of PD-1 is accomplished through a mechanism of providing immune escape for tumor cells by inactivating cytotoxic T cells or inhibiting tumor cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the α‐CD19 synNotch receptor, when stimulated, induced the expression of [PD‐L1‐T2A‐IL‐10] . As the main ligand for PD‐1, PD‐L1 induces a co‐inhibitory signal in activated T‐cells and also stimulates cytokine IL‐10 production, further reducing the immune response …”
Section: Adoptive T‐cell Anti‐cancer Immunotherapymentioning
confidence: 99%